The effectiveness of honey supplementation in feed for improving goldfish fingerling Carassius auratus immune system against Aeromonas hydrophila bacteria attack - Rosidah Rosidah; Ujang Subhan; Yuniar Mulyani; Rifai Dermawan (Jurnal Akuakultur Indonesia)
ABSTRACT